3D crystal plasticity analyses on the role of hard/soft inclusions in the local slip formation. (May 2020) - Fincato, Riccardo; Tsutsumi, Seiichiro; Sakai, Tatsuo; Terada, Kenjiro
Highlights: Role of aluminum oxide and manganese sulphide inclusions in a ferritic matrix. Mesoscale 3D Finite Element analyses with crystal plasticity in a finite strain framework. Plastic slip as a function of the matrix lattice orientation considering an anisotropic elastic ferrite. Investigation of the role of the interface bond between the matrix and the inclusion in the generation of plastic slip. Effect of a superimposed compressive/tensile mean stress in the generation of plastic slip. Abstract: The present work aims to investigate the phenomenon of local plastic slips formation in the surrounding of inclusions by means of 3D finite element analyses from a mesoscale point of view. Isotropic elastic spherical Al2 O3 and MnS inclusions are modelled inside a cylindrical ferritic body subjected to tensile loading conditions with the superimposition of hydrostatic pressure. A crystal plasticity constitutive model within the framework of finite strains is adopted for the description of the matrix together with an anisotropic elasticity tensor. Several crystallographic orientations are considered, in relation to the loading direction, to observe the stress distribution and the formation of the plastic deformation in the surrounding of the inclusion. Two modelling strategies of the matrix-defect interface bond are investigated.